2018
DOI: 10.1371/journal.pgen.1007793
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic STARR-seq reveals how DNA shape and sequence modulate transcriptional output and noise

Abstract: The binding of transcription factors to short recognition sequences plays a pivotal role in controlling the expression of genes. The sequence and shape characteristics of binding sites influence DNA binding specificity and have also been implicated in modulating the activity of transcription factors downstream of binding. To quantitatively assess the transcriptional activity of tens of thousands of designed synthetic sites in parallel, we developed a synthetic version of STARR-seq (synSTARR-seq). We used the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 52 publications
(97 reference statements)
0
25
1
Order By: Relevance
“…For U2OS-GR, the RNA-seq data was from previous studies ( 26 , 27 ), ArrayExpress accession number E-MTAB-6738. U2OS-GR cells were treated for 4h with either 1μM Dex or 0.1% ethanol as vehicle control.…”
Section: Methodsmentioning
confidence: 99%
“…For U2OS-GR, the RNA-seq data was from previous studies ( 26 , 27 ), ArrayExpress accession number E-MTAB-6738. U2OS-GR cells were treated for 4h with either 1μM Dex or 0.1% ethanol as vehicle control.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the precise nucleotide sequence in a GBS is proposed to function as a shaping ligand that specifies GR's transcriptional activity. X-ray crystallography of GR DBD dimers bound to different GBSs showed that conformation of the lever arm in the DBD appeared to be influenced by the DNA sequence (24, 119). Furthermore, the addition of a single GR-binding site was sufficient to convert a gene, which was normally not regulated by GR, into a target gene, such as IL-1 β and IL1R2 in U2OS cells (120).…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq data for U2OS-GR cells was generated as previously described ( 32 ), except that cells were treated with 1 μM dexamethasone for 24 h in addition to the 4-h treatment.…”
Section: Methodsmentioning
confidence: 99%